Impact of right atrial enlargement on clinical outcome in patients with atrial fibrillation - Ko, Kyu-Yong; Jang, Ji-Hun; Choi, Seong-Huan; Baek, Yong-Soo; Kwon, Sung Woo; Park, Sang-Don; Woo, Seong-Ill; Kim, Dae-Hyeok; Shin, Sung-Hee (Frontiers in Cardiovascular Medicine, 2022)
Background Left atrial (LA) remodeling is associated with adverse cardiovascular events, including heart failure (HF) and stroke in patients with atrial fibrillation (AF). However, there are limited data on the value of right atrial (RA) remodeling in this population. We investigated the prognostic role of RA enlargement in patients with nonvalvular AF. Methods and results We analyzed 254 consecutive patients (age=69±12years, male:female=165:89, mean left ventricular ejection fraction=58.0±7.2%) with nonvalvular AF who underwent two-dimensional echocardiography from a single center. RA and LA volumes were measured from apical views and indexed to the body surface areas (right atrial volume index [RAVI] and left atrial volume index [LAVI]) and RAVI > 30mL/m2 and LAVI > 34mL/m2 were considered as enlarged. The relationship between RA enlargement and composite clinical outcome of hospitalization for HF (HHF), stroke, systemic embolism, or death from any cause was assessed. RA enlargement was associated with older age and more frequent prevalence of persistent or permanent AF. During a median follow-up of 47.1 months, 77 patients (30%) had experienced primary composite outcome. In a multivariable model, RA enlargement, but not LA enlargement, was independently associated with adverse clinical outcomes even after adjusting for clinical and echocardiographic factors (adjusted hazard ratio [HR], 1.90 [95% confidence interval (CI), 1.14-3.18], p=0.014 for primary composite outcome; adjusted HR, 2.70 [95% CI, 1.27-5.67], p=0.001 for HHF or all cause death). Conclusion RA enlargement was independently associated with an increased risk of HF, stroke, systemic embolization or death in patients with nonvalvular AF, suggesting that RA volume can be helpful in assessing future cardiovascular risk in this population.